State and outlook of the mining industry - Vasara, Heino (Työ- ja elinkeinoministeriö, 2018)
Mining industry is highly cyclical, influenced by the trends in raw material prices on the world market. The current economic situation of Finnish mines is quite good. Increased mining operations have also created new technology companies and boosted the growth of SMEs. Mines located in Finland constitute a good customer reference for SMEs aiming at the international market. From the perspective of international mining companies the Finnish technology and service providers are often quite small. Networking and collaboration with companies that serve as drivers offer opportunities in internationalisation and passing on sector-specific expertise. The mines improve Finland’s raw material self-sufficiency, but refining of metals in this country is still dependent on raw material imports. The growing threat of resource nationalism is one of the reasons why self-sufficiency in metal concentrates has to be increased to ensure that the operations of the downstream industries will continue. In 2016 the turnover of metal ore and industrial mineral production totalled about EUR 2 billion and it employed directly about 4 500 persons in Finland. In 2016 there were ten active metal ore mines and 27 industrial mineral mines in Finland. Most of the active mines and mining projects are located in eastern and northern Finland. Mining investments totalled about EUR 240 million, showing a clear increase from the year before. Investments in ore prospecting started to grow as well. The society needs mineral raw materials, and without effective ore prospecting no new mines will be opened to replace the depleting mines. Many of the active mines have expanded their operations. In 2016 a total of 28 million tonnes of ore was quarried from the Finnish metal ore mines and the production of usable rock for industrial minerals totalled 15 million tonnes. Measured by the quarrying volume the three largest mines in Finland were Kevitsa, Talvivaara and Siilinjärvi. All of these are open quarries. Mining has long traditions in Finland. The ...